2010
DOI: 10.1038/nature09307
|View full text |Cite|
|
Sign up to set email alerts
|

Heterochromatin silencing of p53 target genes by a small viral protein

Abstract: The transcription factor p53 guards against tumor and virus replication and is inactivated in almost all cancers. p53 activated transcription of target genes is thought to be synonymous with the stabilization of p53 in response to oncogenes and DNA damage. During adenovirus replication, the degradation of p53 by E1B-55k is considered essential for p53 inactivation, and is the basis for p53 selective viral cancer therapies. Here we reveal a dominant epigenetic mechanism that silences p53-activated transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 58 publications
(68 reference statements)
7
127
0
1
Order By: Relevance
“…It has been shown that deleting a small viral protein E4-orf3 can bring higher safety to the oncolytic adenovirus; 22 and liver cancer suppressor gene, such as HCCS1 or SOCS3, Liver cancer-targeting gene-viro-therapy X Liu et al have been shown to specifically inhibit liver tumorigenesis. 19,23 It will be our future interest to improve the presently used HCC-targeting OV Ad Á AFP Á D55 and select more appropriate antitumor genes using these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that deleting a small viral protein E4-orf3 can bring higher safety to the oncolytic adenovirus; 22 and liver cancer suppressor gene, such as HCCS1 or SOCS3, Liver cancer-targeting gene-viro-therapy X Liu et al have been shown to specifically inhibit liver tumorigenesis. 19,23 It will be our future interest to improve the presently used HCC-targeting OV Ad Á AFP Á D55 and select more appropriate antitumor genes using these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…p53 is in fact a powerful transcription factor, and, consequently, it drives a large number of promoters, 7 depending on specific activators. [8][9][10][11] Possibly the most studied promoter target is p21, [12][13][14] but new targets emerge as, for example, the connection between IL-7Ra and telomer erosion 15 or the silencing of repeats and noncoding RNA. 16 As a consequence of the transactivation of so many different promoters so far described, p53 is able to activate different biochemical pathways affecting the regulation of life and death of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Either mechanism alone is sufficient to inhibit a DDR and allow efficient Ad DNA replication to occur. Finally, the E4-ORF3 protein inhibits p53-induced gene expression by establishing heterochromatin at p53-responsive cellular promoter regions (28). The E4-ORF3 and E1B-55K⅐E4-ORF6 proteins are multifunctional and play additional roles in the viral life cycle, including the promotion of cell cycle-independent viral replication, the regulation of viral late mRNA splicing and cytoplasmic mRNA accumulation, and the regulation of late protein translation (29 -37).…”
mentioning
confidence: 99%